Effectiveness of training general practitioners to improve the implementation of brief stop-smoking advice in German primary care: study protocol of a pragmatic, 2-arm cluster randomised controlled trial (the ABCII trial) - Sabrina Kastaun; Verena Leve; Jaqueline Hildebrandt; Christian Funke; Stephanie Becker; Diana Lubisch; Wolfgang Viechtbauer; Olaf Reddemann; Linn Hempel; Hayden McRobbie; Tobias Raupach; Robert West; et al. (BMC Family Practice, 2019)
Abstract Background The German clinical guideline on tobacco addiction recommends that general practitioners (GPs) provide brief stop-smoking advice to their patients according to the “5A” or the much briefer “ABC” method, but its implementation is insufficient. A lack of training is one barrier for GPs to provide such advice. Moreover, the respective effectiveness of a 5A or ABC training regarding subsequent delivery of stop-smoking advice has not been investigated. We developed a training for GPs according to both methods, and conducted a pilot study with process evaluation to optimize the trainings according to the needs of GPs. This study aims at evaluating the effectiveness of both trainings. Methods A pragmatic 2-arm cluster randomised controlled trial with a pre-post data collection will be conducted in 48 GP practices in North Rhine-Westphalia (Germany). GPs will be randomised to receive a 3.5-h-training in delivering either 5A or ABC, including peer coaching and intensive role plays with professional actors. The patient-reported primary outcome (receipt of GP advice to quit: yes/no) and secondary outcomes (recommendation rates of smoking cessation treatments, group comparison (5A versus ABC): receipt of GP advice to quit) will be collected in smoking patients routinely consulting their GP within 4 weeks prior, and 4 weeks following the training. Additional secondary outcomes will be collected at 4, 12 and 26 weeks following the consultation: use of cessation treatments during the last quit attempt (if so) since the GP consultation, and point-prevalence abstinence rates. The primary data analysis will be conducted using a mixed-effects logistic regression model with random effects for the cluster variable. Discussion If the training increases the rates of delivery of stop-smoking advice, it would offer a low-threshold strategy for the guideline implementation in German primary care. Should one method prove superior, a more specific guideline recommendation can be proposed. Trial registration German Clinical Trials Register (DRKS00012786); registered on 22th August 2017, prior to the first patient in.